Knowledge and Acceptability of Anal Cytology Screening Among Women. Issue 1 (January 2016) - Blankenship, Stephanie A.; Debnath, Priyanka; Szlachta-McGinn, Alec W.; Maguire, Karla; Garcia, Jorge J.; Aserlind, Alexandra; Lipshultz, Emma; Potter, JoNell E.
Abstract : Objective: Medical providers have initiated anal cytology screening among women to detect anal neoplasia early. Lack of knowledge of the human papillomavirus (HPV) and anticipated screening discomfort may limit patient acceptance. This study investigates attitudes toward anal cytology screening among women. Materials and Methods: Women seen for gynecologic care at an urban university medical center were invited to complete an anonymous survey assessing their understanding of HPV and interest in anal cytology screening. Subjects reported the level of pain, discomfort, and embarrassment they expected from screening on a 100-mm visual analog scale. Results: Four hundred four women with mean (SD) age 36 (13) years met criteria for participation. Three hundred thirty-five women reported their race: 52% were white and 36% were African American. Three hundred forty-eight women reported their ethnicities: 76% were Hispanic and 12% were Haitian. Twenty-two percent had never heard of HPV, 57% were not familiar with anal cytology screening, 67% acknowledged that screening was very helpful in detecting anal neoplasia early, and 28% were very interested in undergoing screening. Mean (SD) level of anticipated pain, discomfort, and embarrassment during screening was 62 (32), 68 (30), and 58 (34) mm, respectively. Level of familiarity with anal cytology screening ( p < .001), belief in its utility in detecting anal neoplasia ( p < .001), and level of anticipated pain ( p = .004) were significant predictors of acceptability. Conclusions: Medical providers should improve counseling about anal cytology screening among at-risk women to familiarize them with the procedure, describe its role in detecting anal neoplasia, and address expectations surrounding pain to increase its acceptability. Abstract : Anal cytology screening has limited acceptability among urban, underserved, minority women due to limited familiarity with the procedure and anticipated pain during screening. Supplemental digital content is available in the text.